The Believer in One Almighty God and Digital Technology: Case Study on Paguyuban Budaya Bangsa Pusat Kebumen - Priyono, Dedi; Novita Al Ihyak Dieni (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Digital technology has become a core part of daily life, impacting communication, work, and interaction. This shift poses challenges for maintaining spiritual values, especially as it affects how religious beliefs and practices are integrated into modern culture. This is a challenge for believers to be able to accept the development of digital technology by not changing the sacredness of the guidance. This research investigates how members of Paguyuban Budaya Bangsa (PBB), a belief organization in Wonokriyo Village in Kebumen, navigate these challenges, exploring the influence of digital technology on their spiritual teachings, their efforts to preserve traditional doctrines like